Significant detection of new germline pathogenic variants in Australian Pancreatic Cancer Screening Program participants - Krithika Murali; Tanya M. Dwarte; Mehrdad Nikfarjam; Katherine M. Tucker; Rhys B. Vaughan; Marios Efthymiou; Allison Collins; Allan D. Spigelman; Lucinda Salmon; Amber L. Johns; David B. Williams; Martin B. Delatycki; et al. (Hereditary Cancer in Clinical Practice, 2021)
Abstract Background The Australian Pancreatic Cancer Screening Program (APCSP) offers endoscopic ultrasound surveillance for individuals at increased risk of pancreatic ductal adenocarcinoma (PDAC) with all participants requiring assessment by a Familial Cancer Service before or after study enrolment. Methods Individuals aged 40–80 years (or 10 years younger than the earliest PDAC diagnosis) were eligible for APCSP study entry if they had 1) ≥ two blood relatives with PDAC (at least one of first-degree association); 2) a clinical or genetic diagnosis of Hereditary Pancreatitis or Peutz-Jeghers syndrome irrespective of PDAC family history; or 3) a known PDAC predisposition germline pathogenic variant (BRCA2, PALB2, CDKN2A, or Lynch syndrome) with ≥one PDAC-affected first- or second-degree relative. Retrospective medical record review was conducted for APCSP participants enrolled at the participating Australian hospitals from January 2011 to December 2019. We audited the genetic investigations offered by multiple Familial Cancer Services who assessed APCSP participants according to national guidelines, local clinical protocol and/or the availability of external research-funded testing, and the subsequent findings. Descriptive statistical analysis was performed using Microsoft Excel. Results Of 189 kindreds (285 participants), 50 kindreds (71 participants) had a known germline pathogenic variant at enrolment (BRCA2 n = 35, PALB2 n = 6, CDKN2A n = 3, STK11 n = 3, PRSS1 n = 2, MLH1 n = 1). Forty-eight of 136 (35%) kindreds with no known germline pathogenic variant were offered mutation analysis; 89% was clinic-funded, with increasing self-funded testing since 2016. The relatively low rates of genetic testing performed reflects initial strict criteria for clinic-funded genetic testing. New germline pathogenic variants were detected in five kindreds (10.4%) after study enrolment (BRCA2 n = 3 kindreds, PALB2 n = 1, CDKN2A n = 1). Of note, only eight kindreds were reassessed by a Familial Cancer Service since enrolment, with a further 21 kindreds identified as being suitable for reassessment. Conclusion Germline pathogenic variants associated with PDAC were seen in 29.1% of our high-risk cohort (55/189 kindreds; 82/285 participants). Importantly, 10.4% of kindreds offered genetic testing were newly identified as having germline pathogenic variants, with majority being BRCA2. As genetic testing standards evolve rapidly in PDAC, 5-yearly reassessment of high-risk individuals by Familial Cancer Services is warranted.